Towards a Competent Negotiator in the Intercultural Context - Katarzyna Cybulska-Gómez de Celis (University of Social Science, 2020)
As intercultural negotiations appear frequently on the business agenda and involve high-stakes investments, negotiators are expected to possess appropriate competencies. The author opens the article with the intricate nature of negotiations, describing their underlying processes and strategies; subsequently, she discusses the link between negotiations and culture, reviewing studies within this area and underscoring the importance of developing cultural intelligence. Finally, she offers insights into the framework of negotiation competencies and negotiation pedagogy